2019
DOI: 10.1002/ccd.28145
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with peripheral vascular disease following percutaneous coronary intervention

Abstract: Objectives To evaluate the clinical characteristics and outcomes of patients with peripheral vascular disease (PVD) undergoing percutaneous coronary intervention (PCI) in a contemporary setting, and to determine whether use of drug‐eluting stents (DESs) improves outcomes. Background PVD was an independent risk factor for adverse outcomes following PCI in the bare‐metal stent (BMS) era. It is not known whether outcomes in these patients have improved with advances in interventional techniques and stent technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 48 publications
8
24
1
Order By: Relevance
“…Previous studies reported PAD to be present in 5-20% of patients undergoing PCI [6,7,17]. The rate of 6.7% found in our study is within the previously reported range, however, the reported rate of PAD is relatively low.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies reported PAD to be present in 5-20% of patients undergoing PCI [6,7,17]. The rate of 6.7% found in our study is within the previously reported range, however, the reported rate of PAD is relatively low.…”
Section: Discussionsupporting
confidence: 80%
“…Meta analyses of eight randomized PCI trials, found an almost 50% increased 1-year mortality risk independently associated with PAD [19]. Compared with BMS, patients with PAD treated with DES had better cardiovascular outcomes (yet still increased risk of 1-year cardiac death, MI and TVR compared to patients without PAD treated with DES) [7]. Other data from the first-generation DES era reports conflicting outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found an association between the following factors and increased risk of long‐term mortality: higher age, higher baseline SYNTAX score, non‐use of statins at baseline, insulin‐dependent diabetes, COPD, peripheral vascular occlusive disease, and lower baseline platelet count. Peripheral vascular occlusive disease has previously been identified as a risk factor for poor long‐term outcomes after PCI in general 25,26 . Moreover, the conclusion that higher baseline SYNTAX score is associated with long‐term mortality among patients with ESRD is consistent with a study performed by Tomaszuk‐Kazberuk et al validating the prognostic tool among dialysis‐dependent patients 27 .…”
Section: Discussionsupporting
confidence: 79%
“…Further, due to the diffuse nature of the atherosclerotic process, patients with MVCAD are often complicated with PVD. Previous studies have shown that PVD is an independent predictor of adverse outcomes and poorer survival after CABG and PCI [ 25 , 26 ]. Although not statistically significant after multivariate adjustment analysis, there was still an association between PVD and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%